Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan Pada Koperasi Simpan Pinjam Manunggal Makmur Surakarta - Yuwati, Tika, Ma'ruf, Drs., MM (2017)
This study aim to determine the effect of training and motivation on the performance of employees at Credit Unions Manunggal Makmur Surakarta. Samples taken in this study were employees working at Credit Unions manunggal Makmur Surakarta. Distributing questionnaires to 70 respondents employees at Credit Unions Manunggal makmur Surakarta taken by census sampling. Data analysis methods used are validity, realiabilitas test, classic assumption test and test multiple linear regression analysis with t-test, F and coefficient of determination (R 2 ). Hypothesis tests showed the effect of training, and motivation have significant influence with t respectively 4,194 and 4,062. In the F test showed that together the variable training and motivation significantly influence employee performance with a probability value of 0.000 (0.000 <0.05). And the coefficient of determination (R 2 ) of 54,1%.